2018
DOI: 10.1002/pc.24760
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐mechanical characterization of shape‐memory polyurethane nanocomposites filled with carbon nanotubes and graphene nanosheets

Abstract: The shape‐memory materials are nowadays an important subject in the scientific community due to their huge technological potential. In the present study, in order to pursue the mechanical reinforcement and improvement of the shape‐memory thermoplastic polyurethane (TPU) properties, it was conducted an experimental study in which TPU nanocomposites containing carbon based nanoparticles were produced by melt mixing and injection molding. The resulting nanocomposites contained treated and non‐treated multiwalled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The carboxylation of CNT established the linkage between CNT and the matrix and improved the thermal diffusivity of the nanocomposite. Reinforcement of CNT into the natural rubber matrix made the composite susceptible to near-infrared laser irradiation, which actsas a trigger to the shape memory process [ 72 ]. Lai et al melted blended natural rubber/paraffin wax/CNT composite and studied the two-way shape memory effect, which involves melt-induced contraction and cooling-induced elongation behaviour.…”
Section: Shape Memory Materials Of Rubbersmentioning
confidence: 99%
“…The carboxylation of CNT established the linkage between CNT and the matrix and improved the thermal diffusivity of the nanocomposite. Reinforcement of CNT into the natural rubber matrix made the composite susceptible to near-infrared laser irradiation, which actsas a trigger to the shape memory process [ 72 ]. Lai et al melted blended natural rubber/paraffin wax/CNT composite and studied the two-way shape memory effect, which involves melt-induced contraction and cooling-induced elongation behaviour.…”
Section: Shape Memory Materials Of Rubbersmentioning
confidence: 99%
“…Tehran et al 15 blended CNTs with TPU/PBT and indicated that CNTs significantly improved the elastic modulus, tensile and bending strength of TPU/PBT blend. Fonseca et al 16 prepared TPU nanocomposites containing carbon‐based nanoparticles by melting mixing and injection molding. The thermal and mechanical properties of nanocomposites were improved by surface modification of CNT.…”
Section: Introductionmentioning
confidence: 99%
“…Shape memory polymers (SMPs) can be fixed into a temporary shape by external constraint and recovered to initial shapes when exposed to outer stimulus . By molecular structures, SMPs can be divided into many categories: epoxy‐based, styrene‐based, polyurethane (PU)‐based, acrylate‐based, poly(vinyl alcohol) (PVA)‐based, and so on. And some new SMPs, such as polypeptide, chitosan, and poly(vinyl acetate), were also discovered recently.…”
Section: Introductionmentioning
confidence: 99%
“…However, SMPs have some intrinsic drawbacks such as relatively low modulus and low strength, which are common for polymers. To overcome the drawbacks, SMP‐based composites (especially nanocomposites) were developed for enhancing the mechanical properties . Most SMPs are thermo‐triggered, which may be not practical when outer heating sources are not available .…”
Section: Introductionmentioning
confidence: 99%